2008
DOI: 10.1021/jo801948m
|View full text |Cite
|
Sign up to set email alerts
|

Densely Functionalized Chiral Pyrroles from Endocyclic, Exocyclic, and Acyclic Vinyl Sulfone-Modified Carbohydrates

Abstract: A wide range of vinyl sulfone-modified carbohydrates have been prepared as starting materials for the synthesis of polysubstituted chiral pyrroles. All these vinyl sulfones reacted efficiently with ethylisocyanoacetate to generate a plethora of new pyrrole derivatives. Furanosyl rings opened up during pyrrole synthesis, and pyranosyl rings were opened up by reacting the pyrrole with POCl(3)/DMF. This paper also reports one of the most efficient and practical routes for the synthesis of beta-substituted pyrrole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…This strategy has amply been employed by Pathak’s group in the synthesis of a variety of compounds including aminosugars [64], branched-chain sugars [65], isonucleosides [62], and chiral pyrroles [66]. For example, conjugate addition of the anion generated from ethyl isocyanoacetate to vinylsulfone 55 afforded a pyrrole derivative 59 , which by subsequent treatment with POCl 3 /DMF afforded chiral pyrrole 60 (Scheme 14).…”
Section: Reactions Of Hex-2-enopyranosidesmentioning
confidence: 99%
“…This strategy has amply been employed by Pathak’s group in the synthesis of a variety of compounds including aminosugars [64], branched-chain sugars [65], isonucleosides [62], and chiral pyrroles [66]. For example, conjugate addition of the anion generated from ethyl isocyanoacetate to vinylsulfone 55 afforded a pyrrole derivative 59 , which by subsequent treatment with POCl 3 /DMF afforded chiral pyrrole 60 (Scheme 14).…”
Section: Reactions Of Hex-2-enopyranosidesmentioning
confidence: 99%
“…[1] In 2009, Pathak et al reported the synthesis of polysubstituted chiral pyrroles from vinyl sulfone-modified 2,3-unsaturated glycosides (Scheme 1d). [10] However, due to the harsh reaction conditions, the substrate scope is limited to only 12 examples. To extend the reaction generality and applicability, it is envisaged that the NO 2 substitution in the 2,3-unsaturated glycosides would reduce the electronic density of the double bond, which might accelerate the process of the proposed [3 + 2] cycloaddition, therefore, making the reaction more convenient and amiable, as a typical Barton-Zard reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Pathak et al . reported the synthesis of polysubstituted chiral pyrroles from vinyl sulfone‐modified 2,3‐unsaturated glycosides (Scheme 1d) [10] . However, due to the harsh reaction conditions, the substrate scope is limited to only 12 examples.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our research on the designing of strategies for the synthesis of carbocycles7a,7b and heterocycles7c starting from vinyl sulfone‐modified carbohydrates,8 we envisioned that by properly designing acyclic vinyl sulfone‐modified carbohydrates,8b it would be possible to synthesize analogs of carbocycles and heterocycles depicted in Figure 1 and Figure 2. Since carbon and other heteroatomic nucleophiles react efficiently at the electrophilic β‐position of vinylic sulfones,8 we opined that the vinyl sulfone group of the acyclic carbohydrate‐modified vinyl sulfones with a properly positioned leaving group as in A (Scheme ) would be in a position to react with externally delivered nucleophiles preferentially; intermediate B would then intramolecularly attack the carbon atom bearing the mesylate group in S N 2 fashion, causing ring formation with completestereocontrol to afford compound C .…”
Section: Resultsmentioning
confidence: 99%